1993
DOI: 10.1212/wnl.43.1_part_1.176
|View full text |Cite
|
Sign up to set email alerts
|

Mortality risks in gay men with human immunodeficiency virus infection and cognitive impairment

Abstract: We obtained data from 111 gay men who entered a longitudinal study of the natural history of human immunodeficiency virus (HIV) without clinical evidence of acquired immunodeficiency syndrome (AIDS), and examined them regularly over a 36-month period. Using a Cox proportional-hazard regression model to compare cumulative risk of mortality in subjects with and without cognitive impairment and several putative risk factors present at baseline, we found that the mortality risk ratio (RR) associated with poor neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
41
0
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(43 citation statements)
references
References 0 publications
1
41
0
1
Order By: Relevance
“…In the U.S., research prior to aviability of Highly Active Antiretroviral Treatment (HAART) demonstrated that presence of neuropsychological (NP) impairment in HIV infected persons conferred an increased risk early mortality, above and beyond what could be predicted from medical indices of disease progression (Mayeux et al, 1993;Ellis et al, 1997). It is unclear whether NP impairment still produces worse medical outcomes in the context of HAART, but there is considerable evidence that even mild NP impairment is associated with reduced vocational functioning and other difficulties with cognitive aspects of everyday functioning: medication management, driving, and Instrumental Activities of Daily Living (IADLs; Carter et al, 2003;Heaton et al, 2004a;Hinkin et al, 2004;Marcotte et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In the U.S., research prior to aviability of Highly Active Antiretroviral Treatment (HAART) demonstrated that presence of neuropsychological (NP) impairment in HIV infected persons conferred an increased risk early mortality, above and beyond what could be predicted from medical indices of disease progression (Mayeux et al, 1993;Ellis et al, 1997). It is unclear whether NP impairment still produces worse medical outcomes in the context of HAART, but there is considerable evidence that even mild NP impairment is associated with reduced vocational functioning and other difficulties with cognitive aspects of everyday functioning: medication management, driving, and Instrumental Activities of Daily Living (IADLs; Carter et al, 2003;Heaton et al, 2004a;Hinkin et al, 2004;Marcotte et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Future longitudinal research should determine whether patterns of neuropsychological performance are stable and whether they predict differences in neuropsychological change (e.g., worsening) over time and other clinically relevant outcomes, either independently or in concert with level of performance indicators (e.g., the Global Deficit Score). Outcomes of interest include unemployment (Benedict, Mezhir, Walsh, & Hewitt, 2000;Heaton et al, 2004a;Rabkin, McElhiney, Ferrando, Van Gorp, & Lin, 2004), difficulties on performance-based instrumental activities of daily living (Benedict et al, 2000;Heaton et al, 2004a), adherence to prescribed medication regimens (Hinkin et al, 2002;Levine et al, 2005), complaints of cognitive problems in everyday functioning (Heaton et al, 2004a), and early mortality Mayeux et al, 1993). Also of interest is whether the neuropsychological profiles identified here, especially when seen with HIV-infected people who also have impaired overall levels of neuropsychological functioning, will be associated with differential patterns of brain abnormalities on neuroimaging (Ragin et al, 2005;Tucker et al, 2004) and postmortem neuropathology studies (Cherner et al, 2002b;Ellis et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Within the context of HIV infection, results of NP testing have shown robust associations with structural and functional brain imaging (Jernigan et al, 1993;Stout et al, 1998), as well as with postmortem neuropathology findings (Cherner et al, 2002;Everall et al, 1999;Masliah et al, 1997;Moore et al, 2006). Moreover, NP impairment in HIV-infected persons has been shown to be an independent predictor of early mortality Mayeux et al, 1993) and to be strongly predictive of a wide variety of difficulties in activities of daily living (Heaton et al, 2004a).…”
Section: Introductionmentioning
confidence: 99%